Strengthening the Core Values of BerAKHLAK in Agenda 2 Learning of Latsar CPNS BRIN through Assignment Strategies and Innovative Learning Media - Naily Kamaliah; Alpha Fadila Juliana Rahman; Afifudin Ferdiansyah; Niken Rahayu Sepa (Monas: Jurnal Inovasi Aparatur, 2025)
The Basic Training (Latsar) for CPNS at BRIN aims to develop civil servants with integrity through the internalization of BerAKHLAK core values. A key challenge lies in ensuring participants understand and apply these values in their roles as researchers. This study examines the implementation of BerAKHLAK values in Agenda 2 and evaluates the influence of learning media and assignment types on value internalization. A quantitative approach was used with 21 participants. Data were obtained from pre- and post-tests, individual and group assignments, and facilitator assessment rubrics. Analyses included Mann Whitney, Kruskall Wallis, and factor analysis using SPSS 26. Results indicate a significant improvement in value comprehension after training. Learning media had a significant effect, with papers being the most effective. Group assignments were more effective than individual tasks as they fostered collaboration, adaptability, and harmony. Factor analysis revealed one main component, with harmonious values showing the strongest contribution. These findings highlight the importance of assignment design and innovative media. The implication is that BRIN should strengthen varied learning strategies to support character building in civil servants.